Aberrant DNA methylation associated with aggressiveness of gastrointestinal stromal tumour. Issue 3 (27th June 2011) - Okamoto, Yasuyuki; Sawaki, Akira; Ito, Seiji; Nishida, Toshirou; Takahashi, Tsuyoshi; Toyota, Minoru; Suzuki, Hiromu; Shinomura, Yasuhisa; Takeuchi, Ichiro; Shinjo, Keiko; An, Byonggu; Ito, Hidemi; et al.
Abstract : Background and aims: The majority of gastrointestinal stromal tumors (GISTs) have KIT mutations; however, epigenetic abnormalities that could conceivably potentiate the aggressiveness of GISTs are largely unidentified. Our aim was to establish epigenetic profiles associated with the malignant transformation of GISTs. Methods: Methylation of four tumor suppressor genes, RASSF1A, p16, CDH1, and MGMT was analyzed in GISTs. Additionally, genome-wide DNA methylation profiles were compared between small, malignant-prone, and malignant GISTs using methylated GpG island amplification microarrays (MCAM) in a training set (n=40). Relationships between the methylation status of genes identified by MCAM and clinical features of the disease were tested in a validation set (n=75). Results: Methylation of RASSF1A progressively increased from small to malignant GISTs. p16 was specifically methylated in malignant-prone and malignant GISTs. MCAM analysis showed that more genes were methylated in advanced than in small GISTs (average of 473 genes vs 360 genes, respectively, P =0.012). Interestingly, the methylation profile of malignant GISTs was prominently affected by their location. Two genes, REC8 and PAX3, which were newly-identified via MCAM analysis, were differentially methylated in small and malignant GISTs in the training and validation sets. Patients with methylation of at least REC8, PAX3, or p16 had a significantly poorer prognosis ( P =0.034). Conclusion: Our results suggest that GIST is not, in epigenetic terms, a uniform disease and that DNA methylation in a set of genes is associated with aggressive clinical behavior and unfavorable prognosis. The genes identified may potentially serve as biomarkers for predicting aggressive GISTs with poor survivability.